2021
DOI: 10.1101/2021.12.16.472391
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reduced sera neutralization to Omicron SARS-CoV-2 by both inactivated and protein subunit vaccines and the convalescents

Abstract: Omicron variant continues to spread all over the world. There are lots of scientific questions remaining to be answered for such a devastating variant. There are a dozen of vaccines already in clinical use. The very urgent scientific question would be whether or not these vaccines can protect Omicron variant. Here, we tested the sera from both convalescents and vaccine recipients receiving either inactivated or protein subunits vaccines (CoronaVac from Sinovac, or BBIBP-CoV from Sinopharm, or ZF2001 from Zhife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 5 publications
3
12
0
Order By: Relevance
“…The Omicron variant has a total of 30 mutations on the spike protein, and half of the mutations happened on the RBD compared to the ancestral variant B.1, while there are eight mutations for the Delta variant, two of which exist on the RBD [15]. The results in Figure 2 revealed that the Delta variant, with only two mutations on the RBD, has limited decrease in the binding capability of the RBD to both vaccinated sera and convalescent sera, which was consistent to some studies recently [16,17]. However, Omicron evades antibodies elicited by the ancestral variants and by the inactivated vaccine efficiently, with steep reduction in the binding capability of its RBD.…”
Section: Discussionsupporting
confidence: 87%
“…The Omicron variant has a total of 30 mutations on the spike protein, and half of the mutations happened on the RBD compared to the ancestral variant B.1, while there are eight mutations for the Delta variant, two of which exist on the RBD [15]. The results in Figure 2 revealed that the Delta variant, with only two mutations on the RBD, has limited decrease in the binding capability of the RBD to both vaccinated sera and convalescent sera, which was consistent to some studies recently [16,17]. However, Omicron evades antibodies elicited by the ancestral variants and by the inactivated vaccine efficiently, with steep reduction in the binding capability of its RBD.…”
Section: Discussionsupporting
confidence: 87%
“…Omicron quickly outcompeted the circulating Delta variant within weeks after landing in Europe and US, and has become the dominant VOC around the globe. Scientists found that there was a significant reduction in Omicron virus neutralizing activity in sera obtained from individuals infected by pre-Omicron variants and populations vaccinated with immunogens based on early WA-1 virus (Cao et al, 2021; Lee et al, 2022; Zhao et al, 2021). A huge number of breakthrough infections have been reported even from individuals fully vaccinated with the 3 rd booster shot.…”
Section: Introductionmentioning
confidence: 99%
“…GMTs and fold changes were obtained by Webplotdigitzer for Kimpel11 , Corti12 (subset), Gupta13 and Liu14 . The data for Pfizer/BioNTech 15 , Schmidt16 , Israel MoH 17 , HKU18 , Balazs 19 , Gruell20 , Poehlmann21 , Montefiori/Doria-Rose 22 , Ho23 , Schwartz24 , Snape 25 ,Gao26 were directly obtained from the respective manuscripts or reports.…”
mentioning
confidence: 99%